Pengaruh Lifestyle dan Motivasi Terhadap Keputusan Pembelian Produk Motor Nmax di Kota Bima - Sri Ernawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In effort to meet their needs, a person will choose a product that can provide the highest satisfaction and quality of life. The purpose of this study is to determine whether lifestyle and motivation affect purchasing decisions either partially or simultaneously. This type of research is quantitative with a survey approach. The population in this study were all consumers who had bought an Nmax motorcycle in Bima City. The sample used was 100 people with this technique the sampling used in this study was purposive sampling. The data analysis technique used is validity test, reliability test, linear regression test staying up late, determination test, t test and f test. The results showed that lifestyle and motivation had a significant effect on purchasing decisions for NMax motorcycle products, either partially or simultaneously.